ARTICULATION BETWEEN CURRICULUM, METHODOLOGIES AND DIGITAL TECHNOLOGIES: PATHWAYS TO PEDAGOGICAL INNOVATION - Teske, Juciane Salgueiro de Mello (Seven Editora, 2025)
The objective of this article is to investigate the relationship between curricula, methodologies and digital technologies to improve pedagogical mediation and knowledge construction. Through a bibliographical research, works that address curricular innovation and the use of technologies in the educational context were analyzed, making it possible to identify concepts, obstacles and opportunities of this relationship in current education. The analysis revealed that the combination of these elements is crucial for the realization of a more dynamic, inclusive education that is aligned with the needs of 21st century society, emphasizing the value of critical and planned pedagogical mediation by teachers. Obstacles such as inadequate infrastructure, few policies that contribute to innovation and minimal provision of continuing education for teachers were also pointed out. Thus, it is considered that the research made it possible to understand how this relationship contributes to the improvement of pedagogical practice and the advancement of learning, also indicating the possibility for future studies that deepen innovative practices in different school environments, aiming to strengthen a more effective and inclusive education.DOI: https://doi.org/10.56238/sevened2025.038-058